The Early Childhood Oral Health Impact Scale (ECOHIS): psychometric properties and application on preschoolers - Silva, Bianca Núbia Souza [UNESP]; Campos, Lucas A. [UNESP]; Marôco, João; Campos, Juliana A.D.B. [UNESP] (PeerJ, 2023)
Background. The concept of oral health related to quality of life involves the impact that oral health has on an individual’s well-being. The Early Childhood Oral Health Impact Scale (ECOHIS) was developed to measure the impact of oral health problems on the lives of children and their families. Objective. To evaluate the psychometric properties of ECOHIS applied to mothers of preschool children and estimate the influence of demographic characteristics, caries experience, and plaque index on the ECOHIS score. Methods. The fit of ECOHIS to the data was assessed by confirmatory analysis. Chi-square for degrees of freedom ratio (χ2/df), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), and Root Mean Square Error of Approximation (RMSEA) were used. Reliability was estimated by the ordinal coefficients alpha (α) and omega (ω). The factorial invariance was estimated by the difference in CFI (1CFI). Comparisons of the ECOHIS mean scores according to the demographic characteristics, caries experience, and plaque index was performed using analysis of variance (ANOVA). Results. A total of 371 children participated in the study. Mothers’ mean age was 33.0 (SD = 7.04) years. The ECOHIS presented a good fit to the data (χ2/df = 4.31; CFI = 0.95; TLI = 0.94; RMSEA = 0.09) and a strict model invariance. Children without caries and from higher income class had lower oral health impact. Conclusion. The data obtained with the ECOHIS were valid, reliable, and invariant. Children with caries experience and from lower income families had a greater impact of oral problems.
Keywords: Children; Oral health